Wireless communication influence on CNC machine tool probe metrological parameters. Issue 1 (January 2016) - Wozniak, Adam; Jankowski, Michal
Abstract The influence of the wireless communication on CNC machine tools touch-trigger probe inaccuracy of probing is investigated. Factors such as time of processing and wireless transmission of trigger signal from the probe to the CNC machine tool controller including position and orientation of the interface receiver are taken into consideration. A new method allowing to obtain 3D probe error characteristics with several times more accuracy than the procedure used on a CNC machine tools has been applied. The analyses have been performed for several wireless interfaces of two types: an optical and a radio type. The influence of the abovementioned parameters has been analysed theoretically and verified experimentally. Good agreement between the proposed theoretical model and experimental data has been obtained.